A new bombardier beetle species of the genus Brachinus (Coleoptera: Carabidae: Brachininae) from the Western Ghats in south west India with a new synonymy. (3rd July 2021) - M, Divya; Kurian, Ashly; Sabu, K. Thomas
ABSTRACT: Description of a new bombardier beetle species, Brachinus paikadai sp. nov ., first report of B. peltastes Andrewes, 1931 from south India and outside the type locality in Himalaya and synonymisation of B. cinctellus Chaudoir, 1876 with B. limbellus Chaudoir, 1876 are provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:93B7754A-8088-4631-AACD-AA55D48DFED9